The 22nd annual prostate cancer foundation scientific retreat report. Issue 12 (8th June 2016) - Miyahira, Andrea K.; Simons, Jonathan W.; Soule, Howard R.
Abstract : The 22nd Annual Prostate Cancer Foundation (PCF) Scientific Retreat was convened in Washington, D.C. from October 8 to 10, 2015. This event is the foremost scientific conference in the world focusing on basic, translational, and clinical prostate cancer research with the highest potential for accelerating the understanding of prostate cancer biology and improving the lives and outcomes of prostate cancer patients. Topics highlighted during the 2015 Retreat included: (i) new strategies and treatments for localized high‐risk, hormone‐naïve, oligometastatic, castrate‐resistant, and treatment‐refractory prostate cancer settings; (ii) the biology and genomics of tumor heterogeneity and tumor evolution; (iii) new understandings on the mechanisms and targeting of oncogenic drivers of prostate cancer; (iv) bioengineering of novel therapies and drug delivery methods; (v) innovative approaches to tumor immunotherapy; (vi) emerging molecular imaging technologies with improved sensitivity and specificity; and (vii) advancements in prognostic and predictive biomarkers and precision medicine strategies. Prostate 76:1037–1052, 2016 . © 2016 Wiley Periodicals, Inc.